"Ask me about my goals!": challenging pervasive assumptions of gang members’ fatalism by exploring gay gang members’ goals - Panfil, Vanessa R. (Critical criminology, 2022)
Research on gangs and urban communities has often focused on gang members’ alleged fatalism and corresponding lack of aspirations for the future. Relatedly, theories and research regarded as criminological canon can lead to assumptions and misrepresentations that are damaging and dehumanizing. Using examples from an interview-based and partially ethnographic study with gay and bisexual male gang members, I explore their goals for the future, in depth and in context. These men had detailed, specific, and normative goals, such as gaining fulfilling employment, educational attainment, and healthy families, as well as existential goals. Their well-formulated goals demonstrate how cultural messages and mainstream research assumptions can prime gang researchers to overlook or misinterpret our participants’ own motives and meanings. This can be overcome by including gang-involved study participants in the research process and adopting an ethical standpoint of pursuing contextualized, humanistic portrayals of gang-involved people.